Mechanical behavior of cemented paste backfill under the coupled effect of loading rate and moisture content - Chuanchuan Wan; Xiaocong Yang; Jiwei Bian; Wenyuan Xu; Hongwei Shi; Hao Huang (PLoS ONE, 2026)
This study investigates the coupled effects of loading rate and moisture condition on the mechanical behavior of cemented paste backfill (CPB). Uniaxial compression tests were conducted on CPB specimens under dry (0%), nature (18%), and saturated (32%) moisture conditions at loading rates ranging from 0.05 to 2.0 mm/min. The results show that uniaxial compressive strength (UCS) follows a second-order polynomial relation with loading rate and exhibits an overall rise-then-fall trend, with a common transition region around 1.0 mm/min. Relative to the nature condition, the dry condition generally enhances strength and stiffness, whereas the saturated condition weakens them but increases peak strain over the low-to-intermediate loading-rate range. Failure mode is also moisture dependent, with dry specimens showing more brittle behavior and saturated specimens exhibiting more tensile-dominated failure. The nonlinear index is likewise sensitive to loading rate and moisture condition, and saturated CPB exhibits the highest nonlinear index before the transition region. Based on UCPI analysis, the fitted optimal loading rates are 1.20, 1.23, and 0.97 mm/min for the dry, nature, and saturated conditions, respectively. Although the fitted optima differ slightly, they remain clustered around 1.0 mm/min. These findings indicate that loading-rate regulation in underground backfill-supported environments should account for the prevailing moisture condition rather than rely on a single fixed loading-rate criterion.